Localization of T and B Lymphocytes to the White Pulp of the Spleen is Independent of L-, E-, and P-Selectin - Mitchell H. Grayson; David D. Chaplin (The Scientific World Journal)
T and B cell interactions are thought to be of prime importance in the generation of a humoral immune response. These interactions are thought to take place in the secondary lymphoid organs. The largest of which is the spleen. While the pathways involved in lymphocyte migration into other secondary lymphoid organs have been unraveled, very little is understood about T and B cell migration to the spleen. We report that adoptively transferred T lymphocytes appear more rapidly within the lymphoid compartment of the spleen than do B lymphocytes. Indeed, half of the transferred T lymphocytes in the spleen appear within the white pulp by 1.4 hours. B lymphocytes take nearly 4.3 hours to achieve the same level of accumulation. In addition, T lymphocyte arrival is fucoidan sensitive, while B cells are not affected by this polysaccharide. Finally, we show that neither L-, E-, or P-selectin appears to play a significant role in the accumulation of lymphocytes in the white pulp.)